2012
DOI: 10.1113/jphysiol.2012.232777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate increases tetanic [Ca2+]i and contractile force in mouse fast‐twitch muscle

Abstract: Key points Dietary supplementation with inorganic nitrate has beneficial effects on skeletal muscle responses to exercise. Both mitochondrial and extra‐mitochondrial explanations have been proposed. Contractile force of fast‐twitch muscles was enhanced in mice supplemented with 1 mm NaNO3 in drinking water for 7 days. Myoplasmic free [Ca2+] during tetanic stimulation was increased in fast‐twitch muscles of nitrate‐supplemented mice and this was accompanied by increased expression of calsequestrin 1 and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
363
4
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(397 citation statements)
references
References 40 publications
22
363
4
8
Order By: Relevance
“…It was suggested that the decreased ATP turnover occurring after nitrate supplementation might be related to a reduced ATP requirement for actin-myosin cross-bridge cycling and/or calcium handling, given previous reports that NO slows actin-myosin cross-bridge cycling [59,60] and inhibits calcium-ATPase activity [61,62]. Interestingly, a recent murine model investigation reported greater force production, and increased expression of the calcium handling protein calsoquestrin 1 and the dihydropyridine receptor in type II muscle fibres following nitrate supplementation [9]. It was speculated that such effects in humans may allow muscle activation at a lower frequency for an equivalent force production, lowering motor unit recruitment and concomitantly the ATP cost of exercise.…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variamentioning
confidence: 95%
See 4 more Smart Citations
“…It was suggested that the decreased ATP turnover occurring after nitrate supplementation might be related to a reduced ATP requirement for actin-myosin cross-bridge cycling and/or calcium handling, given previous reports that NO slows actin-myosin cross-bridge cycling [59,60] and inhibits calcium-ATPase activity [61,62]. Interestingly, a recent murine model investigation reported greater force production, and increased expression of the calcium handling protein calsoquestrin 1 and the dihydropyridine receptor in type II muscle fibres following nitrate supplementation [9]. It was speculated that such effects in humans may allow muscle activation at a lower frequency for an equivalent force production, lowering motor unit recruitment and concomitantly the ATP cost of exercise.…”
Section: Effect Of Nitrate Supplementation On Cardiorespiratory Variamentioning
confidence: 95%
“…Nitrate supplementation had no effect on severe-intensity cycling TTE in normoxia, but improved TTE by ~ 8.6 % in hypoxia relative to placebo. Further, there is evidence from murine model investigations that nitrate supplementation may enhance tissue blood flow [41,42] and muscle contractile function [9] preferentially in type II muscle fibres. It is therefore possible that nitrate supplementation is more effective during shorter more high-intensity exercise, during which these muscle fibres are more heavily recruited [9,[43][44][45]64], or else in individuals with greater distribution of type II muscle fibres [43].…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 99%
See 3 more Smart Citations